Month Related Anomalies In Indian Stock Market: an Empirical Study: An empirical examination of month related effects on the Bombay stock exchange (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Calendar anomalies inthe stock market has been a topic of vital importance in India and as well asthe rest of the world. Calendar anomalies refer to the significant variationsin the returns of a specific day or time period and the rest of the days andother time periods. Most researched calendar anomalies are weekend effect(Monday effect), Friday effect, Wee-day effect (related to any other days ofthe week), Month related effects such as Monthly effect, turn of month effectand semi month effect etc. This paper examines the month related effects on theBombay stock exchange. The prices of stock markets have been taken from BSESensex (a barometer of Indian stock markets) for the period from 1998 to 2012(excluding the years 2008 and 2009 being the years of abnormal variations). Thedata has been divided in to three time periods viz. 1998 to 2001 (beforerolling settlement), 2002 to 2007 (after rolling settlement but before theyears of abnormal variations) and 2010 to 2012 (after the years of abnormalvariations). The data has been analysed with the help of mean, standarddeviations, t-test and ANOVA.